2019
DOI: 10.3920/bm2019.0068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotic supplementation on cognitive function in children and adolescents: a systematic review of randomised trials

Abstract: Available reviews have shown potential effects of probiotics on neurobehavioral outcomes through ‘gut-brain axis’ mechanism in adults. However, reviews on cognitive function in children and adolescents are lacking. Therefore, we conducted a systematic review of randomised controlled trials (RCTs) of the effect of probiotic supplementation on cognitive function in children and adolescents. A search of four databases (Cochrane Central Register of Controlled Trials, PsycARTICLES, Scopus, PubMed) was conducted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…A recent systematic review included randomized controlled trials, published between 1990 and 2018, that had evaluated the effects of probiotic supplementation on the cognitive function in children and adolescents. Seven studies were found to meet the inclusion criteria, but only one of them reported a significant reduction in the risk to develop ADHD or ASD [195]. This was a double-blind randomized placebo-controlled trial conducted by Pärtty et al [152] on a Finnish population of 159 infants who had at least one family member with allergic disease.…”
Section: Therapeutic Role Of the Gut Microbiome In Adhd: Probioticsmentioning
confidence: 99%
“…A recent systematic review included randomized controlled trials, published between 1990 and 2018, that had evaluated the effects of probiotic supplementation on the cognitive function in children and adolescents. Seven studies were found to meet the inclusion criteria, but only one of them reported a significant reduction in the risk to develop ADHD or ASD [195]. This was a double-blind randomized placebo-controlled trial conducted by Pärtty et al [152] on a Finnish population of 159 infants who had at least one family member with allergic disease.…”
Section: Therapeutic Role Of the Gut Microbiome In Adhd: Probioticsmentioning
confidence: 99%
“…For that reason, the addition of probiotic strains such as L. plantarum 299v has been found to improve cognitive functioning in patients with major depression [8]. Additionally, other lactic bacteria such as L. rhamnosus GG have shown improvements in children's and adolescents' cognitive function, generating the reduction of behavior and communication disorders such as autism [9]. Therefore, the development of next-generation functional foods is crucial to make available to consumers products with beneficial health effects [10].…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are live microorganisms, which, when administered in adequate amounts, confer a health benefit on the host [ 96 , 97 ]. Probiotic supplementation has been widely studied in children presenting various health conditions [ 98 , 99 , 100 , 101 , 102 , 103 , 104 ], whereas there have been very few studies regarding gut microbiota dysbiosis in pediatric patients with cancer. The first one was published in 1980 [ 105 ] and was also one of the first works that examined the concept of intestinal decontamination, that is, a prophylactic strategy that consists of the administration of antimicrobials with limited anaerobicidal activity in order to reduce the burden of aerobic gram-negative bacteria and/or yeast in the intestinal tract and so prevent infections caused by these organisms.…”
Section: Dysbiosis and Cancer In Childrenmentioning
confidence: 99%